BMI1 enables interspecies chimerism with human pluripotent stem cells. Issue 1 (December 2018) - Huang, Ke; Zhu, Yanling; Ma, Yanlin; Zhao, Bentian; Fan, Nana; Li, Yuhang; Song, Hong; Chu, Shilong; Ouyang, Zhen; Zhang, Quanjun; Xing, Qi; Lai, Chengdan; et al.
Abstract Human pluripotent stem cells (hPSCs) exhibit very limited contribution to interspecies chimeras. One explanation is that the conventional hPSCs are in a primed state and so unable  to form chimeras in pre-implantation embryos. Here, we show that the conventional hPSCs undergo rapid apoptosis when injected into mouse pre-implantation embryos. While, forced-expression of BMI1, a polycomb factor in hPSCs overcomes the apoptosis and enables hPSCs to integrate into mouse pre-implantation embryos and subsequently contribute to chimeras with both embryonic and extra-embryonic tissues. In addition, BMI1 also enables hPSCs to integrate into pre-implantation embryos of other species, such as rabbit and pig. Notably, BMI1 high expression and anti-apoptosis are also indicators for naïve hPSCs to form chimera in mouse embryos. Together, our findings reveal that the apoptosis is an initial barrier in interspecies chimerism using hPSCs and provide a rational to improve it. Conventional human pluripotent stem cells (hPSCs) fail to contribute to interspecies chimaeras when injected into mouse blastocysts. Here the authors show that forced expression of BMI1 overcomes apoptosis of hPSCs in blastocysts of mouse, rabbit and pig allowing them to contribute to chimaeras.